Application of fuzzy controllers in the autopilot of an unmanned aerial vehicle - Penghao Gu; A. A. Lobaty (Системный анализ и прикладная информатика, 2024)
The article is devoted to the study of the features of the application of regulators built on the use of theoretical provisions of fuzzy logic, when creating autopilots of unmanned aerial vehicles (UAVs). The substantiation of the principles and methods of synthesizing a mathematical model of an autopilot as applied to a multi-rotor UAV, the features of the application of various mathematical models of regulators, their advantages and disadvantages is carried out. A reasonable conclusion is made that the use of traditional approaches based on the use of linear mathematical models of the control object does not ensure the required quality of control in a wide range of UAV application conditions in the presence of restrictions and external influences on the control process. It is proposed to use the principles and methods of fuzzy mathematics, which underlie the increasingly widespread fuzzy logic controllers (FL controllers), when constructing a mathematical model of a UAV autopilot. The construction of a UAV control channel based on the use of a fuzzy logic controller is considered, and a description of the controller structure implemented in the SiminTech computer environment is given. Using mathematical modeling, a comparison was made of the performance and transient characteristics of the NL controller with the PID controller and the P controller as applied to the control system of one of the UAV channels – the roll control channel. It has been established that fuzzy logic controllers used as elements of UAV autopilots, compared to other controllers, provide the necessary quality of transient processes in the UAV control system with resistance to undesirable external influences, which makes these controllers promising for use in nonlinear non-stationary control systems for moving objects, which include UAVs.